Living Wages and the Welfare State : The Anglo-American Social Model in Transition - Wilson, Shaun, 1971- (Book collections on Project MUSE., 2021)
Addressing the rapidly shifting politics of the minimum wage in six English-speaking countries, Shaun Wilson analyses minimum wage policies within a political-economy narrative. Topical and poignant, this book identifies the success of living wage campaigns as central to both welfare state change and alternatives to the Basic Income.